Collaborative Governance dalam Meningkatkan Indeks Kebahagiaan Masyarakat (Index of Happiness) di Kota Bandung - Agustina, Winda; Wulandari, Widuri (Jurnal Pemerintahan dan Politik, 2023)
This study aims to determine collaborative governance in increasing the index of people's happiness in the city of Bandung. The happiness index for the city of Bandung has increased from 2014 to 2018. However, in 2019-2020 there was no measurement of the happiness index in the city of Bandung. The community happiness index in 2019-2020 can experience a decline, this is due to the impact of 10 community happiness index benchmarks in the city of Bandung. This research uses the theory from Ansel and Gash which looks at governance collaboration in 4 stages namely initial conditions, institutional design, facilitative leadership, and collaboration processes. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results of this study indicate that: 1) the initial conditions, collaboration can be carried out by both parties according to needs, 2) there is no specific institutional design that houses the happiness index, 3) the Bandung City Cooperation Field acts as an intermediary between the government and the collaborating parties, 4) there has been a collaboration of municipal, group and individual internal governance.